Analysis of clinical characteristics and factors influencing herpes simplex virus keratitis - Zhang, Shuai; Mi, Jinhua; Ge, Shengmei; Wang, Guoqiang; Zhou, Zhongyou; Zhao, Yantao; Zhao, Yan (Frontiers in Medicine, 2024)
Objective To investigate the clinical characteristics and factors associated with herpes simplex virus keratitis. Methods Patients with herpes simplex virus keratitis who came to our hospital from January 2018 to June 2022 were selected and divided into a good prognosis group and a poor prognosis group according to their prognosis. The clinical data of the two groups were compared, and univariate/multivariate logistic regression was used to analyze the factors influencing the poor prognosis of herpes simplex virus keratitis. Results A one-way analysis of variance showed that, compared with the good prognosis group, the poor prognosis group had more elderly patients and a longer course of disease, and the difference was statistically significant (p < 0.05). There were significant differences in the types of patients between the two groups (p < 0.05). Univariate logistic regression analysis also showed that age (≥65 years) (OR: 1.557, 95%CI: 1.081–2.183, p < 0.05), course of disease (> 7 months) (OR: 1.303, 95%CI: 1.003–1.829, p < 0.05), epithelial type (OR: 2.321, 95%CI: 1.198–4.321, p < 0.05), and stromal type (OR: 2.536, 95%CI: 1.672–3.871, p < 0.05) were risk factors for poor prognosis. Multivariate logistic regression analysis showed that age (≥65 years) (OR: 1.656, 95%CI: 1.168–2.357, p < 0.05) and course of disease (> 7 months) (OR: 1.461, 95%CI: 1.031–2.001, p < 0.05) were independent risk factors for the prognosis of herpes simplex keratitis. Conclusion The clinical symptoms of herpes simplex virus keratitis include corneal opacity, corneal posterior elastic layer folds, corneal infiltration, posterior corneal mass, corneal edema, and ocular pain. Age and course of disease are important factors in the prognosis of herpes simplex virus keratitis.